Bioorthogonal probes for imaging sterols in cells - Jao, Cindy Y. (Chembiochem, 2015)
Cholesterol is a fundamental lipid component of eukaryotic membranes and a precursor of potent signaling molecules, such as oxysterols and steroid hormones. Cholesterol and oxysterols are also essential for Hedgehog signaling, a pathway critical in embryogenesis and cancer. Despite their importance, imaging sterols in cells is currently very limited. We introduce a robust and versatile method for sterol microscopy based on C-19 alkyne cholesterol and oxysterol analogs. These sterol analogs are fully functional: they rescue growth of cholesterol auxotrophic cells and faithfully recapitulate the multiple roles that sterols play in Hedgehog signal transduction. Alkyne sterol analogs incorporate efficiently into cellular membranes and can be imaged with high resolution via copper(I)-catalyzed azide-alkyne cycloaddition. We demonstrate the use of alkyne sterol probes for visualizing the subcellular distribution of cholesterol, and for two-color imaging of sterols and choline phospholipids. Our imaging strategy should be broadly applicable to studying the role of sterols in normal physiology and disease.